Effectiveness of gaseous CO2 fertilizer application in China's greenhouses between 1982 and 2010. (September 2015) - Xin, Ma; Shuang, Liu; Yue, Li; Qinzhu, Gao
Graphical abstract: Highlights: Gaseous CO2 fertilizers enhanced the yield of representative fruit vegetable by 33.31% in China. Crop maturity advanced by average of 6.87 days using gaseous CO2 fertilizers. Good linear relationship between yields of cucumber and chili and application of CO2 fertilizers. Abstract: The biological utilization of CO2 represents a promising application for carbon capture, utilization, and storage (CCUS) technologies. The Technical Assessment Report of Carbon Dioxide Utilization in China recommends gaseous fertilization in greenhouses as an important technological use of CO2 . However, the effectiveness of gaseous CO2 fertilizers at increasing crop yields unpredictable due to varying climatic and technological conditions in China. Here, we analyzed 188 articles on gaseous CO2 fertilization technology in China published from 1982 to 2010. We found that gaseous CO2 fertilizers enhanced the yield of representative fruit vegetable (i.e., cucumber, tomato, chili, zucchini, eggplant, and strawberry) by 33.31% over the past three decades. In addition, crop maturity also advanced (by an average of 6.87 days) and crop resistance to diseases and pests was enhanced. We observed a relatively good linear relationship between crop yield increases and increased CO2 fertilizer application for cucumber and chili once 240.0–3042.75 kg gaseous CO2 fertilizer was applied per hectare. For the other four crops, a positive correlation was observed. The mean increase in the yield of the six fruit vegetables supports the Technical Assessment Report of Carbon Dioxide Utilization in China, which adopted a 30% increase in yield by gaseous CO2 fertilizers to calculate the economic benefits of this technique. Finally, we suggest that methods of fertilization and business modes of gaseous CO2 fertilizer application that fit practical farming conditions in China should be proposed to serve as references for the development of gaseous CO2 fertilization for CCUS engineering.